Comparing local control and distant metastasis in NSCLC patients between CyberKnife and conventional SBRT. (March 2020) - Diamant, André; Heng, Veng Jean; Chatterjee, Avishek; Faria, Sergio; Bahig, Houda; Filion, Edith; Doucet, Robert; Khosrow-Khavar, Farzin; Naqa, Issam El; Seuntjens, Jan
Highlights: CyberKnife delivers higher dose outside PTV compared to conventional SBRT (VMAT/CRT). Higher dose outside the PTV is associated with reduced distant metastasis recurrence rates in CyberKnife. Multivariate analysis revealed that threshold dose was of significant importance in predicting distant metastasis. CyberKnife was found to provide superior local control than conventional SBRT. Abstract: Background and Purpose: Previous literature suggests that the dose proximally outside the PTV could have an impact on the incidence of distant metastasis (DM) after SBRT in stage I NSCLC patients. We investigated this observation (along with local failure) in deliveries made by different treatment modalities: robotic mounted linac SBRT (CyberKnife) vs conventional SBRT (VMAT/CRT). Materials and methods: This study included 422 stage I NSCLC patients from 2 institutions who received SBRT: 217 treated conventionally and 205 with CyberKnife. The dose behavior outside the PTV of both sub-cohorts were compared by analyzing the mean dose in continuous shells extending 1, 2, 3, …, 100 mm from the PTV. Kaplan-Meier analysis was performed between the two sub-cohorts with respect to DM-free survival and local progression-free survival. A multivariable Cox proportional hazards model was fitted to the combined cohort (n = 422) with respect to DM incidence and local failure. Results: The shell-averaged dose fall-off beyond the PTV was found to be significantly more modest in CyberKnife plans than in conventional SBRT plans. In a 30 mm shell around the PTV, the mean dose delivered with CyberKnife (38.1 Gy) is significantly larger than with VMAT/CRT (22.8 Gy, p < 10 - 8 ). For 95% of CyberKnife plans, this region receives a mean dose larger than the 21 Gy threshold dose discovered in our previous study. In contrast, this occurs for only 75% of VMAT/CRT plans. The DM-free survival of the entire CyberKnife cohort is superior to that of the 25% of VMAT/CRT patients receiving less than the threshold dose ( VMAT / CRT < 21 Gy ), with a hazard ratio of 5.3 (95% CI: 3.0–9.3, p < 10 - 8 ). The 2 year DM-free survival rates were 87% (95% CI: 81%–91%) and 44% (95% CI: 28%–58%) for CyberKnife and the below-threshold dose conventional cohorts, respectively. A multivariable analysis of the combined cohort resulted in the confirmation that threshold dose was a significant predictor of DM(HR = 0.28, 95% CI: 0.15–0.55, p < 10 - 3 ) when adjusted for other clinical factors. CyberKnife was also found to be superior to the entire VMAT/CRT with respect to local control (HR = 3.44, CI: 1.6–7.3). The 2-year local progression-free survival rates for the CyberKnife cohort and the VMAT/CRT cohort were 96% (95% CI: 92%–98%) and 88% (95% CI: 82%–92%) respectively. Conclusions: In standard-of-care CyberKnife treatments, dose distributions that aid distant control are achieved 95% of the time. Although similar doses could be physically achieved by conventional SBRT, this is not always the case with current prescription practices, resulting in worse DM outcomes for 25% of conventional SBRT patients. Furthermore, CyberKnife was found to provide superior local control compared to VMAT/CRT.